2018
DOI: 10.1177/0091415018763401
|View full text |Cite
|
Sign up to set email alerts
|

Optimism, Pessimism, Coping, and Depression: A Study on Individuals With Parkinson’s Disease

Abstract: Few published studies exist on how individuals with Parkinson's disease (PD) deal with their disease. We conducted this study to examine the relationship between optimism, pessimism, coping strategies, and depressive symptoms in individuals with PD. Specifically, we assessed the possible mediator role of optimism and pessimism on the relation between coping strategies and depressive symptoms in those with PD. Seventy individuals with PD (35 females and 35 males) were assessed with the Brief COPE scale, Life Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…We observed a gender-specific distribution of active and passive strategies, in concordance with previous studies. 26 33 While men used both active and passive forms of coping to the same extent, women predominantly used passive coping strategies. However, the effect strength was low, so we do not assume that gender is a highly relevant factor for coping in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a gender-specific distribution of active and passive strategies, in concordance with previous studies. 26 33 While men used both active and passive forms of coping to the same extent, women predominantly used passive coping strategies. However, the effect strength was low, so we do not assume that gender is a highly relevant factor for coping in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Pessimism was positively related with depression and anxiety (Giardini et al, 2017;Kwok & Gu, 2017;Scott-Hamilton, & Schutte, 2016), stress (Jones, Lehman, Kirsch, & Hennessy, 2017), and psychological health during pandemic (Arslan, Yıldırım, Tanhan, Buluş, &Allen, 2020). Optimism was also associated with subjective well-being (Herero & Extremera, 2010), psychological well-being (Scheier, Carver, & Bridges, 2001), coping (Anzaldi, & Shifren, 2019), posttraumatic growth (Britton, LaLonde, Oshio, & Taku, 2019), negative emotions (Wrosch & Scheier, 2003), and functioning (Brenes, Rapp, Rejeski, & Miller, 2002). The optimism-pessimism have also manifested their effects on mental health in longitudinal studies.…”
Section: Mediating and Moderating Role Of Optimismmentioning
confidence: 99%
“…Some authors report that women use more emotion-focused coping strategies while men prefer focusing on avoidant coping (60,61). However, a study targeting coping strategies among people with PD reported the opposite, with women reporting more problem-focused coping strategies compared to males (10). Interestingly, less polarized gender roles might associate with better quality of life in women.…”
Section: Gender Aspects In Coping and Informal Carementioning
confidence: 99%
“…As the disease progresses, sex, and gender differences can emerge in the incidence of clinical features, such as postural instability or depressive symptoms (8,9). In addition to these differences in clinical phenotype, coping styles may also vary between men and women with PD (10). Given this broad spectrum of potential differences, the consideration of sex-and gender-specific problems and needs of people with PD appears to be essential to provide personalized care.…”
Section: Introductionmentioning
confidence: 99%